If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5s = 5 + -4s Solving -5s = 5 + -4s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '4s' to each side of the equation. -5s + 4s = 5 + -4s + 4s Combine like terms: -5s + 4s = -1s -1s = 5 + -4s + 4s Combine like terms: -4s + 4s = 0 -1s = 5 + 0 -1s = 5 Divide each side by '-1'. s = -5 Simplifying s = -5
| 8=5/x-8 | | 6x-12=18x+6-12x | | -154=-5(8+4x)+x | | (6y-7)=-1 | | 8(1/4x-1/4) | | -82=5x-2 | | -6=-n | | 18q-19=12-18+19q | | 2x-6x-6=90 | | -6=n | | 4+4k=-8+k | | -300=-20p | | (4t-8)=20 | | -8n-5n=26 | | 20=-n+6n | | p=15-3Qs | | 910x-12=23 | | -13z+2=-14z+20 | | 24/4x3 | | 2(r+1)-r=-2+4 | | 103x+34=52 | | -3y+4=10 | | .87/1 | | 9/2z-7/3=41/6 | | -5-5j=-4j | | K-14=-18 | | -54=16x+312 | | 4(x+5)=3(x-11) | | (5h+2)=-8 | | 3g-8=-2+2g-10 | | 25=x-16 | | -3h+12=-7h-9-16 |